Interactive effects of rice bran compost and chemical fertilizers on macronutrients, oil and protein content in sunflower (Helianthus annuus L.) (International Journal of Agricultural Research, Innovation and Technology, 2021)
A field experiment was conducted at the research farm of Charfasson Govt. College, Bhola, Bangladesh in rabi season in 2015-2016 to evaluate the impact of conjunctive use of chemical fertilizers with rice bran on concentration, uptake and seed quality of sunflower cv. BARI-2 (Keroni-2). The experiment was laid out in the randomized complete block design (RCBD) having sixteen treatments with three replications. The size of the plots were 3 m x 2 m. Treatments were T1 Control (- RB and -NPK), T2: 2.5 t RB ha-1, T3: 5.0 t RB ha-1,T4: 7.5 t RB ha-1, T5: N40P30K50 kg ha-1,T6: N80P60K100 kg ha-1, T7: N120P90K150 kg ha-1, T8: 2.5 t RB ha-1 + N40P30K50 kg ha-1, T9: 2.5 t RB ha-1 + N80P60K100 kg ha-1, T10: 2.5 t RB ha-1 + N120P90K150 kg ha-1, T11: 5.0 t RB ha-1 + N40P30K50 kg ha-1, T12: 5.0 t RB ha-1 + N80P60K100 kg ha-1, T13: 5.0 t RB ha-1 + N120P90K150 kg ha-1, T14: 7.5 t RB ha-1 + N40P30K50 kg ha-1, T15: 7.5 t RB ha-1 + N80P60K100 kg ha-1, T16: 7.5 t RB ha-1 + N120P90K150 kg ha-1. Results showed that the concentration, uptake and quality of seeds (oil and protein) of the crop increased with increasing rate of the amendments significantly (P